Evaluating Multiple Narratives Beyond Nationalist, Colonialist, Imperialist Archaeologies - Habu, Junko; Fawcett, Clare; Matsunaga, John M. (Springer New York : Imprint: Springer, 2008)
Evaluating Multiple Narratives: Beyond Nationalist, Colonialist, Imperialist Archaeologies Edited by Junko Habu, Clare Fawcett, and John M. Matsunaga This volume uses Bruce Trigger's 1984 article, "Alternative Archaeologies: Nationalist, Colonialist, Imperialist" as a starting point to examine the complex interaction between contemporary society and archaeological practice today. It deals with the evaluation of multiple interpretations of the past, with a focus on the concept of multivocality. According to its practitioners and adherents, archaeological multivocality gives voice to underrepresented groups and individuals by providing alternative interpretations of the past. This book uses case studies from Asia, Latin America, Europe and North America to explore the interplay between the sociopolitical context of specific national, regional or local archaeological traditions and the variety of interpretations of the past made by archaeologists and others. A key question asked throughout the book is whether multivocality, a concept derived from postmodern theory and embedded in the political, social and intellectual traditions of Britain and North America, is welcome or applicable in other parts of the world. The diversity of topics and geographical areas covered in the chapters allows readers to understand the dynamic nature of the relationship between archaeology, sociopolitical conditions, and peoples' identities in regional and historical settings. The volume concludes with discussions by Alison Wylie, Ian Hodder, and Bruce Trigger who revisit past research but also look forward to the future of alternate archaeologies, multivocality and multiple narratives.